Research Progress of Worm Gear Material in Worm Drive - Zhang Yanjun; Xu Yong; Ma Xiaoyan; Li Wenbo; Zhang Jianfeng; Song Aiping (Jixie chuandong)
Worm drive has a large transmission ratio，compact structure and stable transmission，thus，it has been widely used in the field of mechanical manufacturing.Bronze is the most common and widespread worm gear material in the worm drive.In order to solve the problems of poor wear resistance，low fatigue strength and scuffing of bronze worm gear，the research of replacement materials bronze worm gear has attracted increasing attention.The common metal materials of bronze worm gear and the research progress concerning alternative materials of bronze worm gear are reviewed.Steel worm gear，cast iron worm gear，zinc aluminum alloy worm gear，and plastic worm gear in domestic and overseas published literatures are mainly discussed.Finally，expectations about materials，surface engineering technology and coating preparation are proposed in respect of current research.